2013
DOI: 10.1136/vr.100782
|View full text |Cite
|
Sign up to set email alerts
|

Influences on antimicrobial prescribing behaviour of veterinary practitioners in cattle practice in Ireland

Abstract: Guidelines on prudent antimicrobial use in veterinary medicine have been developed to reduce inappropriate prescribing of antimicrobials. Such guidelines focus mainly on the clinical and pharmacological indications for prescribing. A questionnaire study of veterinary surgeons engaged in cattle practice was completed to determine if non-clinical issues influence the decision to prescribe antimicrobials, and to assess if pharmacological and non-pharmacological issues influence the choice of antimicrobial prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 17 publications
6
85
2
3
Order By: Relevance
“…Before the introduction of a vaccine in 2006, Porcine Circovirus (PCV2) generally persisted in the herds and the control of PMWS was directed at secondary infections and at associated co-factors for disease (Gibbons et al, 2013;Marshall and Levy, 2011;Segalés et al, 2005) The reason for the observed 10% increase from 2011 to 2012 remains unknown, but the patterns in antimicrobial use indicate a partial reversal of the preceding decrease,i.e. generally related to the same age groups, administration route and agents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Before the introduction of a vaccine in 2006, Porcine Circovirus (PCV2) generally persisted in the herds and the control of PMWS was directed at secondary infections and at associated co-factors for disease (Gibbons et al, 2013;Marshall and Levy, 2011;Segalés et al, 2005) The reason for the observed 10% increase from 2011 to 2012 remains unknown, but the patterns in antimicrobial use indicate a partial reversal of the preceding decrease,i.e. generally related to the same age groups, administration route and agents.…”
Section: Discussionmentioning
confidence: 96%
“…This has been investigated in a few European questionnaire studies (Busani et al, 2004;Gibbons et al, 2013;Vandeweerd et al, 2012;de Briyne et al, 2013). Among non-clinical factors, the owner's expectations of receiving a prescription was reported to affect the veterinarian's decision to treat the animals (Gibbons et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Interview topic guides and the online survey questionnaire were informed by a rapid literature review (Alarcon, 2013;BfR, 2015;Buller et al, 2015;Coyne et al, 2014;De Briyne et al, 2016;Dean et al, 2015;European Commission, 2005, 2010Fontané, 2015;Gibbons, 2013;Hughes, Hermans and Morgan, 2008;Jan et al, 2012;Laanen et al, 2014;Moreno, 2014;Schulze-Geisthövel et al, 2016;Speksnijder et al, 2014 andSwinkels, 2015;and Visschers et al, 2015).…”
Section: Approach and Methodologiesmentioning
confidence: 99%
“…Although veterinarians are usually responsible for choosing the appropriate antimicrobials for treatments, choices may also be influenced by farmers' own opinions and needs based on, for example, cost and profit margin, ease of medicine administration and withdrawal period (De Briyne et al, 2013;Gibbons et al, 2013). Then, once prescribed, little is known on how medicines are administered and managed by the farmers and whether alternative practices are taken into consideration by the farmer to reduce reliance on antibiotics.…”
Section: Introductionmentioning
confidence: 99%